2022
DOI: 10.1021/acschembio.2c00486
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Prenylomic Profiling in the Brain of a Transgenic Mouse Model of Alzheimer’s Disease Reveals Increased Prenylation of a Key Set of Proteins

Abstract: Dysregulation of protein prenylation has been implicated in many diseases, including Alzheimer’s disease (AD). Prenylomic analysis, the combination of metabolic incorporation of an isoprenoid analogue (C15AlkOPP) into prenylated proteins with a bottom-up proteomic analysis, has allowed the identification of prenylated proteins in various cellular models. Here, transgenic AD mice were administered with C15AlkOPP through intracerebroventricular (ICV) infusion over 13 days. Using prenylomic analysis, 36 prenylate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 92 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, we recently identified ALDH9A1 as a protein with increased levels of prenylation in Alzheimer’s disease. 49 Since prenylation of ALDH9A1 on the catalytic residue Cys288 must inhibit its activity, this observation may provide a link between oxidative stress, neuroinflammation and Alzheimer’s disease. 50…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we recently identified ALDH9A1 as a protein with increased levels of prenylation in Alzheimer’s disease. 49 Since prenylation of ALDH9A1 on the catalytic residue Cys288 must inhibit its activity, this observation may provide a link between oxidative stress, neuroinflammation and Alzheimer’s disease. 50…”
Section: Resultsmentioning
confidence: 99%
“…54 Interestingly, we recently identified ALDH9A1 as a protein with increased levels of prenylation in AD. 55 Since prenylation of ALDH9A1 on the catalytic residue Cys288 must inhibit its activity, this observation may provide a link between oxidative stress, neuroinflammation and Alzheimer's disease. 56 As a final point, it is worth noting that protein prenylation typically results in membrane localization.…”
Section: Mechanistic Interpretation and Biological Implicationsmentioning
confidence: 99%
“…Ras oncogenic mutants are associated with 90-95% of certain cancers ( ), and oncogenic phenotypes are altered when CaaX modification is disrupted ( Bergo et al, 2002 ; Cox et al, 2015 ; Sousa et al, 2008 ; Winter-Vann and Casey, 2005 ). In addition to cancer, CaaX proteins are functionally implicated in numerous other disease states including Alzheimer's disease, progeria, liver disease, and viral infections such as hepatitis D and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ( Jeong et al, 2022 ; Marakasova et al, 2017 ; Soveg et al, 2021 ; Wickenhagen et al, 2021 ; Yang et al, 2012 ; Zhao et al, 2020 ). A recent example demonstrating the importance of protein prenylation for viral infection resulted from studies of OAS1 gene splice variants, which concluded that humans expressing a prenylated variant of the Oas1 protein had higher innate antiviral protection against Sars-CoV-2 than those expressing the non-prenylated protein ( Soveg et al, 2021 ; Wickenhagen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%